A new calnexin modulates antibacterial immune response in obscure puffer Takifugu obscurus. (February 2022) - Huang, Ying; Wang, Rui-Xia; Jiang, Fu-Hui; Xu, Xiao-Tong; Shi, Yan; Zhao, Zhe
Abstract: Calnexin (Cnx) is a membrane-bound lectin chaperone of the endoplasmic reticulum. In this study, a novel Cnx homologue from the obscure puffer Takifugu obscurus was characterized, tentatively named ToCnx . The cDNA of ToCnx was 1803 bp, and it contained an open reading frame encoding a polypeptide of 600 amino acid residues with a calculated molecular weight of 67.5 kDa. Multiple alignment of the deduced amino acid sequences of ToCnx and other related fish Cnxs revealed that ToCnx had typical characteristics of fish Cnxs. Sequence comparison and phylogenetic tree analysis showed that ToCnx had the closest relationship with Cnxs from Takifugu flavidus and Takifugu rubripes . ToCnx transcripts were detected in all the tissues examined, and they were mainly expressed in the liver, kidney, and intestine. Upon Vibrio harveyi, Edwardsiella tarda, and Aeromonas hydrophila infection, ToCnx transcripts were all significantly upregulated in the kidneys. The recombinant calreticulin domain of ToCnx (rToCnx) was prepared by prokaryotic expression. In the absence of calcium, rToCnx was able to bind three Gram-negative bacteria ( V. harveyi, E. tarda, and A. hydrophila ) and two bacterial saccharides, such as lipopolysaccharide and peptidoglycan. In the presence of calcium, rToCnx could agglutinate all the detected microorganisms. In addition, rToCnx possessed the effect of inhibiting the growth of three microbe strains. These observations suggested that ToCnx is an important participant in host immune defense against bacteria. Highlights: A calnexin gene was identified in Takifugu obscurus. ToCnx was significantly upregulated following bacterial challenge. rToCnx possessed agglutination ability to Gram-negative bacteria. rToCnx bound to three Gram-negative bacteria and two polysaccharides. rToCnx inhibited the growth of bacteria.